Symbolism of the US battlefield cross: how boots, rifles, and helmets reinforce masculinity - Dundes, Lauren (Frontiers in Sociology, 2023)
This paper explores unconscious symbolism of the battlefield cross memorial for fallen soldiers that consists of combat boots and a rifle, often with dog tags attached, topped by a helmet. While the memorial’s manifest function is to provide solace, build solidarity and convey respect for patriotic sacrifice in response to grief, the battlefield cross also exalts masculinity at a subliminal level. Because of the latent ways in which the components of the battlefield cross reinforce masculinity, the memorial has the potential to encourage a masculine script that treats virility as sacrosanct. The resonance of the battlefield cross and its synergism with unrecognized gender coding in broader society illustrate how a powerful symbol intended to honor members of the military also valorizes machismo, an interpretation that could help explain impediments to women achieving parity with men in the military.